2007
DOI: 10.1073/pnas.0707416104
|View full text |Cite|
|
Sign up to set email alerts
|

EGF receptor ubiquitination is not necessary for its internalization

Abstract: Ubiquitination of the EGF receptor (EGFR) has been implicated in EGF-induced receptor internalization, lysosomal degradation, and down-regulation. Mutation of EGFR ubiquitination sites identified by mass spectrometry yielded receptor mutants that are weakly ubiquitinated and not down-regulated by EGF. However, these EGFR mutants were normally internalized. To examine whether this internalization was mediated by the residual ubiquitination, systematic mutagenesis of lysine residues in the kinase domain of the E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
165
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(184 citation statements)
references
References 28 publications
17
165
2
Order By: Relevance
“…Thus, several mechanisms that impair Cbl targeting to the EGFR and inhibit its downregulation could promote transformation by generating an increase in total levels and surface levels of the EGFR. New data by Sorkin and coworkers show that EGFR ubiquitination is not required for internalization but plays a role in the targeting of the EGFR to late endosomes and multivesicular bodies for degradation, providing additional mechanistic detail on the role of Cbl in EGFR downregulation (Huang et al, 2007). Interestingly, activated Cdc42 sequesters Cbl away from the EGFR and inhibits its downregulation (Wu et al, 2003).…”
Section: How Cancer Hijacks the Epp Machineriesmentioning
confidence: 99%
“…Thus, several mechanisms that impair Cbl targeting to the EGFR and inhibit its downregulation could promote transformation by generating an increase in total levels and surface levels of the EGFR. New data by Sorkin and coworkers show that EGFR ubiquitination is not required for internalization but plays a role in the targeting of the EGFR to late endosomes and multivesicular bodies for degradation, providing additional mechanistic detail on the role of Cbl in EGFR downregulation (Huang et al, 2007). Interestingly, activated Cdc42 sequesters Cbl away from the EGFR and inhibits its downregulation (Wu et al, 2003).…”
Section: How Cancer Hijacks the Epp Machineriesmentioning
confidence: 99%
“…At lower concentrations of EGF the degradation is mediated by CME where ubiquitination is not required before internalization whereas at higher concentrations of EGF, CME is also active but a considerable number of activated EGFR molecules are degraded by NCE (non-clathrin endocytosis). In NCE pathway the degradation takes place in three steps that involves ubiquitination, internalization and proteasome mediated degradation, whereas in CME pathway the ubiquitination step is omitted (Huang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Many yeast surface proteins have been demonstrated to require ubiquitination for their internalization (15), but the situation is less clear in mammals. In the case of the EGF receptor, mutation of multiple intracellular lysines within the kinase domain of the protein leads to an almost complete loss of EGF receptor ubiquitination but did not result in the decrease of its internalization rate (16). Regarding Notch ligands, it has been shown that the E3 ligase Mind Bomb 1 promotes ubiquitination and internalization of mammalian Dll1 (17).…”
Section: Several Authors Have Reported That Ubiquitination and Endocymentioning
confidence: 99%